Evaluasi Pemilihan Electric Submersible Pump (ESP) Untuk Menggantikan Gas Lift (GL) Di Sumur X Lapangan Offshore Y - Nugroho Marsiyanto; Eko Prastio; Aly Rasyid (Fakultas Teknik Universitas Bhayangkara Jakarta Raya, 2022)
Well X is located in the offshore Y field, where there are 7 production wells, all of which use an artificial lift in the form of a gas lift. In this field, oil is produced from the N oil layer while the gas layer comes from the K layer. Well X was drilled in May 2013 with a target of N oil formation at a depth of 9,007 ft MD, slope (450) and 4-1/2